Preparation method and application of MOF-74 with hollow structure
By introducing a hollow structure in MOF-74, using ZIF-8 particles as a template to form an amorphous hollow structure and converting it into crystalline state by hydrothermal method, the problem of low Kr/Xe separation efficiency in the prior art is solved, and Kr is realized The improvement of /Xe adsorption separation rate and the retention of separation performance have promoted the application of MOF materials in Kr/Xe gas separation.
Patent Information
- Application Number
- CN202411500619.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2024-12-31
AI Technical Summary
In the prior art, the Kr/Xe separation efficiency is low, and the separation kinetics lacks research, making it difficult to effectively improve the separation efficiency in industrial gas separation.
By synthesizing ZIF-8 particles with uniform size as a sacrificial template, it is dissolved during the MOF-74 synthesis process to form an amorphous hollow structure, and then converted into crystalline state by hydrothermal method to obtain MOF-74 with hollow structure, thereby Shorten the diffusion distance of gas inside the crystal and increase the adsorption and separation rate of Kr/Xe.
The adsorption separation rate of Kr/Xe is significantly improved, while retaining the excellent separation performance of MOF-74 on Kr/Xe, potentially promoting the application of MOF materials in Kr/Xe gas separation.
Smart Images

Figure CN119219937A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of porous materials and gas separation, and specifically relates to a preparation method of MOF-74 with a hollow structure and application thereof. Background Art
[0002] The increasing demand for energy has prompted people to seek clean energy to replace fossil fuels, and nuclear power is fully developed and widely used today due to its efficient and economical implementation. However, xenon (Xe) and krypton (Kr) are considered "golden gases" and have important applications in industrial and medical fields such as imaging, anesthesia, and lighting for traffic systems. Therefore, it becomes very meaningful to capture and reuse these gases in an effective way. Among them, materials with advanced pore structures have been evaluated as potential alternatives for separating Xe / Kr mixtures from waste gas effluents of nuclear reprocessing plants due to their economic and energy-saving characteristics. Many types of porous materials, such as organic cages, modified zeolites, and activated carbons, have been extensively studied for radioactive Kr / Xe separation, but their adsorption capacity is low.
[0003] Metal-organic framework (MOF) materials are a class of inorganic-organic hybrid porous materials with great potential for molecular separation. Compared with traditional adsorption materials (such as zeolites, activated carbon, molecular sieves and porous alumina, etc.), MOF not only has a larger specific surface area, but also has a diversity of structure and performance due to the almost unlimited combination possibilities between its metal ions and organic ligands. Therefore, MOF materials are often used in column separation to meet the challenges of many gas separations, including CO2 / N2, C2H2 / CO2, C2H4 / C2H6, C2H2 / C2H4, C3H6 / C3H8 and C4H6 / C4H8.
[0004] MOF-74 is one of the MOF materials with high performance for Kr / Xe separation. This type of material is composed of metal ions (Mg 2+ 、Zn 2+ 、Ni 2+ 、Co 2+ , Fe 2+ , Mn 2+ and Cu 2+ A series of MOF materials ( Figure 1), which has a regular hexagonal one-dimensional pore with a size of about 1.1nm and parallel to the c-axis. Since MOF-74 contains a high density of open metal sites that can interact strongly with Xe gas, it has a high adsorption capacity for Xe and has good Kr / Xe separation performance with a separation ratio of up to 10. At present, many in-depth studies have been conducted in the field of thermodynamics to improve the adsorption capacity of MOF-74, but there is little research on the separation kinetics, which is also crucial in industrial gas separation. Therefore, it is very necessary to develop a new structure of MOF-74 material to improve the Kr / Xe separation efficiency.
[0005] In view of this, the existing technology needs to be improved and enhanced. Summary of the invention
[0006] The present invention provides a preparation method of MOF-74 with a hollow structure and application thereof, the main purpose of which is to solve the problem of low Kr / Xe separation efficiency in the prior art.
[0007] In a first aspect, in order to achieve the above-mentioned object, the present invention provides a method for preparing MOF-74 having a hollow structure, wherein the method comprises:
[0008] Synthesis of ZIF-8 particles with uniform size;
[0009] The ZIF-8 particles are used as sacrificial templates and dissolved during the synthesis of MOF-74 to obtain MOF-74 with an amorphous hollow structure;
[0010] The shell layer of the amorphous hollow-structured MOF-74 is converted from an amorphous state to a crystalline state by a hydrothermal method, thereby obtaining MOF-74 with a hollow structure.
[0011] Preferably, the method for preparing MOF-74 having a hollow structure, wherein the synthesis of ZIF-8 particles having uniform size specifically comprises:
[0012] 12.48mmol 2-methylimidazole and 0.624mmol zinc acetate are dissolved in 5-15ml deionized water by ultrasonic dissolution; then stirred at room temperature for 30-60min to obtain ZIF-8 particles with uniform size; wherein the reaction temperature is 20-40°C, and the reaction solvent is water.
[0013] Preferably, the method for preparing MOF-74 having a hollow structure, wherein the ZIF-8 particles are used as sacrificial templates and dissolved during the synthesis of MOF-74 to obtain the hollow structure, specifically comprises:
[0014] ZIF-8 particles were added into a mixed solution of 2,5-dihydroxyterephthalic acid, metal nitrate, acetic acid and sodium hydroxide as a regulator to obtain amorphous hollow structured MOF-74.
[0015] Preferably, in the preparation method of MOF-74 with a hollow structure, the size of the ZIF-8 particles is 0.5-1.5 μm; the reaction solvent is a mixture of water, ethanol and N,N-dimethylformamide, and the volume ratio of the three is 0.5-1:1-2:1-2; the mass ratio of the ZIF-8 particles to water is 0.1-0.5; the mass ratio of the ZIF-8 particles to 2,5-dihydroxyterephthalic acid is 0.05-0.15; the reaction temperature is 80-100°C; and the reaction time is 15-60 min.
[0016] Preferably, the preparation method of MOF-74 with a hollow structure, wherein the MOF-74 is selected from one of Mg-MOF-74, Zn-MOF-74, Ni-MOF-74, Co-MOF-74, Fe-MOF-74, Mn-MOF-74 and Cu-MOF-74.
[0017] Preferably, the preparation method of MOF-74 with a hollow structure, wherein the conversion of the amorphous hollow structure MOF-74 shell from an amorphous state to a crystalline state by a hydrothermal method specifically comprises: obtaining by adding the synthesized amorphous hollow structure MOF-74 to a mixed solution of 2,5-dihydroxyterephthalic acid and acetic acid regulator; wherein the reaction temperature is 80-130°C; the reaction time is 12 to 24 hours; and the mass ratio of the amorphous hollow structure MOF-74 to 2,5-dihydroxyterephthalic acid is 0.5 to 1.
[0018] Preferably, in the method for preparing MOF-74 with a hollow structure, the shell thickness of the amorphous hollow structure MOF-74 is 200 to 400 nm.
[0019] An application of the above-mentioned MOF-74 with a hollow structure, wherein it is used to increase the adsorption and separation rate of MOF-74 for Kr / Xe.
[0020] Preferably, in the application of the MOF-74 having a hollow structure, the adsorption kinetics evaluation of the adsorption separation rate is evaluated by a static adsorption instrument; and the column separation test is evaluated by a gas penetration system.
[0021] The present invention discloses a preparation method and application of a MOF-74 with a hollow structure, wherein the preparation method comprises: first, synthesizing ZIF-8 particles with uniform size; then using the ZIF-8 particles as sacrificial templates to be dissolved while MOF-74 is synthesized to obtain an amorphous hollow structure MOF-74; then converting the amorphous hollow structure MOF-74 shell from an amorphous state to a crystalline state by a hydrothermal method to obtain a MOF-74 with a hollow structure. The MOF-74 with a hollow structure improves the Kr / Xe separation efficiency. The adsorption separation rate of Kr / Xe is improved by shortening the diffusion distance of the gas inside the crystal, while retaining the excellent separation performance of MOF-74 itself for Kr / Xe. This method can potentially promote the application of MOF materials in Kr / Xe gas separation, and has a good prospect for promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for use in the description of the embodiments of the present invention will be briefly introduced below. Obviously, the accompanying drawings in the following description are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative labor.
[0023] Figure 1 The present invention is a flow chart of the preparation method of MOF-74 with a hollow structure.
[0024] Figure 2 This is the SEM image of the solid Ni-MOF-74 synthesized in the present invention.
[0025] Figure 3 SEM, TEM, PXRD, STEM and element distribution spectra of ZIF-8 and Hollow AMC synthesized in the present invention.
[0026] Figure 4 These are the SEM, TEM, STEM and element distribution spectra of Ni-MOF-74(h) synthesized in the present invention.
[0027] Figure 5a Schematic diagram of the adsorption curves of ZIF-8, Ni-MOF-74, Hollow AMC and Ni-MOF-74(h) crystals synthesized in the present invention under N2-77K.
[0028] Figure 5b The pore size distribution diagram of the crystals of ZIF-8, Ni-MOF-74, Hollow AMC and Ni-MOF-74(h) synthesized in the present invention.
[0029] Figure 6 Schematic diagram of the evaluation of the adsorption performance and separation efficiency of Ni-MOF-74 and Ni-MOF-74(h) synthesized in the present invention for Kr and Xe.
[0030] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0031] In order to enable those skilled in the art to better understand the technical solution of the present disclosure, and to fully understand and implement how the present disclosure applies technical means to solve technical problems and achieve the corresponding technical effects, the technical solution in the embodiments of the present disclosure will be clearly and completely described below in conjunction with the drawings in the embodiments of the present disclosure. Obviously, the described embodiments are only embodiments of a part of the present disclosure, not all of the embodiments. The embodiments of the present disclosure and the various features in the embodiments can be combined with each other without conflict, and the technical solutions formed are all within the scope of protection of the present disclosure. Based on the embodiments in the present disclosure, all other embodiments obtained by ordinary technicians in this field without making creative work should fall within the scope of protection of the present disclosure.
[0032] It should be noted that the terms "first", "second", etc. in the specification and claims of the present disclosure and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchangeable where appropriate, so that the embodiments of the present disclosure described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, device, product or equipment that includes a series of steps or units is not necessarily limited to those steps or units clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or equipment.
[0033] When the embodiments give numerical ranges, it should be understood that, unless otherwise specified in the present invention, both endpoints of each numerical range and any numerical value between the two endpoints can be selected. Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those generally understood by those skilled in the art. In addition to the specific methods, equipment, and materials used in the embodiments, according to the grasp of the prior art by those skilled in the art and the record of the present invention, any methods, equipment, and materials of the prior art similar or equivalent to the methods, equipment, and materials described in the embodiments of the present invention can also be used to realize the present invention.
[0034] In the prior art, the focus is mainly on improving the separation efficiency by improving the gas adsorption capacity of MOF materials through thermodynamics, but there is little research on the separation kinetics, which is also crucial in industrial gas separation. In order to ensure high separation performance while improving the Kr / Xe adsorption separation efficiency of MOF materials, the applicant provides a method for constructing a hollow MOF structure to shorten the gas mass transfer distance to increase the gas mass transfer rate, thereby achieving an improvement in the Kr / Xe adsorption separation efficiency.
[0035] The first aspect of the present invention provides a method for preparing a MOF-74 material having a hollow structure, thereby shortening the mass transfer rate of gas inside the crystal, thereby increasing the adsorption and separation rate of MOF-74 for Kr / Xe.
[0036] The second aspect of the present invention provides a performance evaluation of the hollow MOF-74 material for Kr / Xe adsorption and separation. The adsorption rate of Kr and Xe gases is significantly improved compared with solid MOF-74. Through column separation, it is found that the Kr / Xe adsorption and separation efficiency is higher than that of solid MOF-74. This result shows that this method can potentially promote the application of MOF materials in Kr / Xe gas separation.
[0037] like Figure 1 As shown, the present application embodiment provides a method for preparing MOF-74 having a hollow structure, the method comprising:
[0038] S1, synthesis of ZIF-8 particles with uniform size;
[0039] S2, using the ZIF-8 particles as sacrificial templates to be dissolved during the synthesis of MOF-74 to obtain MOF-74 with an amorphous hollow structure;
[0040] S3. Converting the amorphous hollow structure MOF-74 shell from an amorphous state to a crystalline state by a hydrothermal method, thereby obtaining a MOF-74 with a hollow structure.
[0041] Specifically, ZIF-8 particles with uniform size are synthesized by hydrothermal method. ZIF-8 is then used as a sacrificial template and dissolved while MOF-74 is synthesized to obtain a hollow structure. Here, the poor acid-base stability of ZIF-8 is utilized to epitaxially grow a layer of MOF-74 while etching and dissolving. The amorphous shell is then converted into a crystalline shell by hydrothermal method. The adsorption rate of MOF-74 for Kr and Xe can be evaluated by adsorption kinetics. The separation rate of MOF-74 for Kr / Xe can also be evaluated by column separation performance.
[0042] In a specific embodiment, the sacrificial template is ZIF-8, the ligand is 2-methylimidazole, and the inorganic ligand is zinc acetate (abbreviated as Zn(OAc)2).
[0043] In a specific embodiment, the reaction temperature of step S1) is room temperature, and the reaction solvent is water.
[0044] In a specific embodiment, the size of ZIF-8 is 0.5 to 1.5 μm, and its pores are
[0045] In a specific embodiment, the ligand of the MOF-74 series material is selected from 2,5-dihydroxyterephthalic acid (abbreviated as DOT), the inorganic ligand is selected from hydrated nitrate ligand, and the cation is selected from Mg 2+ 、Zn 2+ 、Ni 2+ 、Co 2+ , Fe 2+ , Mn 2+ and Cu 2+ One of them.
[0046] In a specific embodiment, the reaction solvent of step S2) is a mixture of water, ethanol and N,N-dimethylformamide.
[0047] In a specific embodiment, the method of converting the amorphous state into crystalline MOF-74 in step S3) is achieved by adding DOT and acetic acid as a regulator.
[0048] In a specific embodiment, the reaction temperature of step S3) is 120°C.
[0049] In a specific embodiment, the reaction solvent in step S3) is N,N-dimethylformamide.
[0050] In a specific embodiment, the thickness of the MOF-74 shell is 200 to 400 nm.
[0051] The technical solution and technical effects of the present application are further explained below through specific implementation methods.
[0052] Example 1
[0053] This example is the preparation of solid Ni-MOF-74.
[0054] Preparation of Ni-MOF-74: 3mmol Ni(OAC)2·4H2O (746.52mg) and 3mmol DOT (594.39mg) were added to a mixed solution of 30mL THF and 30mL deionized water and dissolved by ultrasonic. The mixed solution was then transferred to a 100mL reaction vessel and reacted in an oil bath at 110℃ for 6h under magnetic stirring (600rpm). After the reaction, the synthesized product was washed 3 times with DMF and anhydrous methanol respectively. Figure 1As shown, the synthesized solid Ni-MOF-74 particles are about 600 nm.
[0055] Example 2
[0056] This example is the preparation of hollow Ni-MOF-74.
[0057] Preparation of ZIF-8: Dissolve 12.48mmol (1.025g) 2-methylimidazole and 0.624mmol Zn(OAc)2 (0.137g) in 15ml deionized water and dissolve by ultrasonic. Then stir at room temperature for 1 hour. After the reaction is completed, wash the synthesized product with DMF and anhydrous ethanol three times respectively. Then disperse ZIF-8 in anhydrous ethanol for use. Figure 2 As shown, the synthesized solid Ni-MOF-74 particles are approximately 1.2 μm.
[0058] Preparation of amorphous hollow Ni-MOF-74 (Hollow AMC for short): 0.05mmol DOT (9.9mg) and 0.45mmol Ni(NO3)2·6H2O (130.9mg) were dissolved in 0.688mL DMF, and then 14.25μL acetic acid and 0.375mL 1M NaOH aqueous solution (0.375mmol) were added to the mixture and stirred (500rpm) for 5 minutes. After mixing, 100mg of the synthesized ZIF-8 was dispersed in 0.6ml ethanol under ultrasound. The prepared solution was transferred to a 20mL reaction vessel, heated to 100°C in an oil bath, and magnetically stirred (600rpm) for 0.5 hours. After the reaction was completed, the synthesized product was washed 3 times with DMF and anhydrous methanol, respectively. Figure 2 As shown, the synthesized amorphous hollow structure shell is flocculent with a thickness of 250 nm. From the TEM-EDS and powder diffraction (PXRD) patterns, we found that the obtained structure is amorphous.
[0059] Preparation of crystalline hollow Ni-MOF-74 (referred to as Ni-MOF-74 (h)): 0.365mmol DOT (72.3mg) and 14.25μL acetic acid were dissolved in 5.0mL DMF and stirred at 500rpm for 5 minutes, and then 50mg of the above-synthesized hollow amorphous Ni-MOF-74 was added to the solution and dispersed under ultrasonic dispersion. The solution was then heated in an oven at 120°C for 12-24h. After cooling to room temperature, the product was collected by centrifugation and washed three times with DMF and anhydrous methanol respectively. Figure 3 The shell thickness of the synthesized hollow structure is ~250nm and becomes rough. TEM-EDS and powder diffraction (PXRD) prove that the amorphous state of the shell is transformed into a crystalline state.
[0060] Characterization of hollow Ni-MOF-74 crystal properties: Figure 4 As shown in Figure 2, the N2 adsorption isotherm at 77K shows that the BET surface area of Ni-MOF-74(h) (885.1cc / g) is more than twice that of hollow AMC (406.3cc / g). However, its BET specific surface area is slightly lower than that of solid Ni-MOF-74 (1076cc / g), which is due to the fact that some residual zinc remains in the cavity of Ni-MOF-74(h) after etching ZIF-8, which has been confirmed by EDS spectra and line scan results ( Figure 3 ). The pore size distribution analysis of Ni-MOF-74(h) shows that its micropores are between 9 nm and 12 nm, which is basically consistent with the micropore distribution of Ni-MOF-74 ( Figure 4 ). All these results indicate that hollow AMC has been successfully transformed into hollow Ni-MOF-74.
[0061] Evaluation of the adsorption kinetics of Kr and Xe on hollow Ni-MOF-74: Then, we studied the adsorption kinetics of Xe on Ni-MOF-74 and Ni-MOF-74(h) by the pressure decay method. The constant surface concentration model (also known as the Fickian diffusion model) was used to fit the kinetic Xe adsorption curve, and the value of Ds / r2 (where Ds is the diffusion coefficient and r is the diffusion length) was calculated. D / r2 represents the gas adsorption rate. As shown in Figure 5, the faster pressure change of Ni-MOF-74(h) indicates faster adsorption kinetics. The value of D / r2 of Ni-MOF-74(h) is 6.66×10-2s-1, which is nearly 3 times that of Ni-MOF-74 (2.56×10-2s-1). This is mainly due to the shorter pore length of Ni-MOF-74(h) compared with Ni-MOF-74, which leads to a shorter gas diffusion distance. Therefore, it can be reasonably concluded that shortening the pore size of MOF-74 crystals to form a hollow structure will lead to a faster Xe adsorption rate. At the same time, it can be seen from Figure 5 that the adsorption amount and selectivity of Ni-MOF-74(h) for Kr and Xe are not reduced.
[0062] Evaluation of Kr / Xe separation efficiency of hollow Ni-MOF-74: To further evaluate how the adsorption kinetics of Ni-MOF-74(h) affects its column separation performance, we conducted breakthrough experiments in a fixed bed column. As shown in the breakthrough curves obtained in Figure 5, due to the faster adsorption kinetics of Xe in Ni-MOF-74(h), the breakthrough curve of Ni-MOF-74(h) is significantly steeper than that of Ni-MOF-74(s). If we define the column breakthrough time (tb) as the time when the outlet CO2 concentration reaches 1000ppm, the Ni is calculated.
[0063] In summary, the present invention discloses a preparation method and application of a MOF-74 with a hollow structure, wherein the preparation method comprises: first, synthesizing ZIF-8 particles with uniform size; then using the ZIF-8 particles as a sacrificial template to be dissolved while MOF-74 is synthesized to obtain an amorphous hollow structure MOF-74; then converting the amorphous hollow structure MOF-74 shell from an amorphous state to a crystalline state by a hydrothermal method to obtain a MOF-74 with a hollow structure. Among them, the MOF-74 with a hollow structure improves the Kr / Xe separation efficiency. The adsorption separation rate of Kr / Xe is improved by shortening the diffusion distance of the gas inside the crystal, while retaining the excellent separation performance of MOF-74 itself for Kr / Xe. This method can potentially promote the application of MOF materials in Kr / Xe gas separation, and has a good prospect for promotion and application.
[0064] It should be noted that in the present disclosure, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, an element limited by the sentence "includes a ..." does not exclude the existence of other identical elements in the process, method, article or device including the element.
[0065] The embodiments described above are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention, and should all be included in the protection scope of the present invention.
[0066] It should be noted that if software tools or components other than those of our company appear in the embodiments of the present application, they are only used for illustrative purposes and do not represent actual use.
Claims
1. A method for preparing MOF-74 having a hollow structure, characterized in that: The method comprises: Synthesis of ZIF-8 particles with uniform size; The ZIF-8 particles are used as sacrificial templates and dissolved during the synthesis of MOF-74 to obtain MOF-74 with an amorphous hollow structure; The shell layer of the amorphous hollow-structured MOF-74 is converted from an amorphous state to a crystalline state by a hydrothermal method, thereby obtaining MOF-74 with a hollow structure.
2. The method for preparing MOF-74 having a hollow structure according to claim 1, characterized in that: The synthesis of ZIF-8 particles with uniform size specifically comprises: 12.48mmol 2-methylimidazole and 0.624mmol zinc acetate are dissolved in 5-15ml deionized water by ultrasonic dissolution; then stirred at room temperature for 30-60min to obtain ZIF-8 particles with uniform size; wherein the reaction temperature is 20-40°C, and the reaction solvent is water.
3. The method for preparing MOF-74 having a hollow structure according to claim 1, characterized in that: The method of using the ZIF-8 particles as sacrificial template to be dissolved during the synthesis of MOF-74 to obtain a hollow structure specifically includes: ZIF-8 particles were added into a mixed solution of 2,5-dihydroxyterephthalic acid, metal nitrate, acetic acid and sodium hydroxide as a regulator to obtain amorphous hollow structured MOF-74.
4. The method for preparing MOF-74 having a hollow structure according to claim 3, characterized in that: The size of the ZIF-8 particles is 0.5-1.5 μm; the reaction solvent is a mixture of water, ethanol and N,N-dimethylformamide, and the volume ratio of the three is 0.5-1:1-2:1-2; the mass ratio of the ZIF-8 particles to water is 0.1-0.5; the mass ratio of the ZIF-8 particles to 2,5-dihydroxyterephthalic acid is 0.05-0.15; the reaction temperature is 80-100°C; and the reaction time is 15-60 min.
5. The method for preparing MOF-74 having a hollow structure according to claim 1, characterized in that: The MOF-74 is selected from one of Mg-MOF-74, Zn-MOF-74, Ni-MOF-74, Co-MOF-74, Fe-MOF-74, Mn-MOF-74 and Cu-MOF-74.
6. The method for preparing MOF-74 having a hollow structure according to claim 1, characterized in that: The method of converting the amorphous hollow structure MOF-74 shell from an amorphous state to a crystalline state by a hydrothermal method specifically includes: obtaining the amorphous hollow structure MOF-74 by adding the synthesized amorphous hollow structure MOF-74 to a mixed solution of 2,5-dihydroxyterephthalic acid and acetic acid as a regulator; wherein the reaction temperature is 80-130°C; the reaction time is 12 to 24 hours; and the mass ratio of the amorphous hollow structure MOF-74 to 2,5-dihydroxyterephthalic acid is 0.5 to 1.
7. The method for preparing MOF-74 having a hollow structure according to claim 1, characterized in that: The shell thickness of the amorphous hollow structure MOF-74 is 200-400 nm.
8. An application of MOF-74 having a hollow structure as claimed in claim 1, characterized in that: Used to improve the adsorption and separation rate of MOF-74 for Kr / Xe.
9. The use of MOF-74 having a hollow structure as claimed in claim 8, characterized in that: The adsorption kinetics of the adsorption separation rate is evaluated by a static adsorption instrument; the column separation test is evaluated by a gas penetration system.
Citation Information
Cited By
Cuboid zeolite imidazate skeleton-8 nanoparticles as well as preparation method and application thereof
CN120535766A
A cuboid zeolitic imidazolate framework-8 nanoparticle and a preparation method and application thereof
CN120535766B
